ALM 2.0: Collaboration and sharing as central concepts in Web 2.0 and Library 2.0 - Dunsire, Gordon (Array, 2008)
The workshop covered theoretical possibilities and practical examples of using online tools and services such as wikis, mashups, Google and Flickr to improve collaboration between archives, libraries, and museums, and their users. Examples included using GoogleMaps to identify and locate cultural information services, using the semantic web to share authority files, using wikis for collaborative projects, and using Flickr to interact with users